Genetic Analysis Shows that Morphology Alone Cannot Distinguish Asian Carp Eggs from Those of Other Cyprinid Species. (31st August 2016) - Larson, James H.; Grace McCalla, S.; Chapman, Duane C.; Rees, Christopher; Knights, Brent C.; Vallazza, Jon M.; George, Amy E.; Richardson, William B.; Amberg, Jon
Abstract: Fish eggs and embryos (hereafter collectively referred to as "eggs") were collected in the upper Mississippi River main stem (~300 km upstream of previously reported spawning by invasive Asian carp) during summer 2013. Based on previously published morphological characteristics, the eggs were identified as belonging to Asian carp. A subsample of the eggs was subsequently analyzed by using molecular methods to determine species identity. Genetic identification using the cytochrome‐ c oxidase 1 gene was attempted for a total of 41 eggs. Due to the preservation technique used (formalin) and the resulting DNA degradation, sequences were recovered from only 17 individual eggs. In all 17 cases, cyprinids other than Asian carp (usually Notropis sp.) were identified as the most likely species. In previously published reports, a key characteristic that distinguished Asian carp eggs from those of other cyprinids was size: Asian carp eggs exhibited diameters ranging from 4.0 to 6.0 mm and were thought to be much larger than the otherwise similar eggs of native species. Eggs from endemic cyprinids were believed to rarely reach 3.0 mm and had not been observed to exceed 3.3 mm. However, many of the eggs that were genetically identified as originating from native cyprinids were as large as 4.0 mm in diameter (at early developmental stages) and were therefore large enough to overlap with the lower end of the size range observed for Asian carp eggs. Researchers studying the egg stages of Asian carp and other cyprinids should plan on preserving subsets of eggs for genetic analysis to confirm morphological identifications. Received July 30, 2015; accepted April 22, 2016 Published online August 31, 2016